Legal Analysis Of The Judge's Consideration On The Matter “Marriage Dispensation From The Perspective Of Justice” - Susanti, Restika (NEGREI: Academic Journal of Law and Governance, 2024)
This study aims to examine the judge's considerations in granting, cannot accept or reject a marriage dispensation application at the Religious Court, and whether the considerations reflectprinciples of justice, legal certainty, and legal benefits. Dispensation Marriage is a mechanism that parents submit to the court to allowing children under the minimum age of marriage to marry. However, early often has negative impacts both physically, psychological, and social for children who carry it out. This study uses a research method with a normative empirical type, a descriptive research type by explaining existing problems, and a problem-solving approach. judicial case study or reviewing cases in several court decisions that have been taken in relation to marriage dispensation. The results of the study show that Judge in various cases of marriage dispensation considered the following factors: such as mental readiness, health, and long-term social impacts forwho married at a young age. Some decisions that were rejected and unacceptable marriage dispensation is based on the principle of child protection and long-term welfare, while the decisiwoitnh to accept the dispensation taking into account emergency situations or very urgent conditions. Conclusion from this study is that not all of the judge's considerations in granting permission for marriage dispensation always reflect justice for children, but there must be justice for parents, social. The suggestion from this research is that is needed cooperation between institutions such as the Ministry of Religion, the Department of Education, and the Departmentof Child Protection to minimize the practice of underage marriage, strengthening protection for children and educational efforts, socialization regarding dangers of underage marriage in order to create a prosperous generation, educated, healthy in the future.